Effects of elasticity parameter definition for real-time pricing remuneration considering different user types - Corsi, Pierfrancesco (2021)
In the last decade Demand Response (DR) programs have been influencing loads’ profiles of electric users who participate in these programs. The evolution of the simulations able to study them brought to the possibility of defining new models that can consider power consumption profiles for different types of user (MAT, AT, MT, BTE, BTN-2, BTN-1) but, in order to better match consumption and production energy curves, highly precise predictions of loads’ profiles are still needed. This goal can be achieved also thanks to the study of the price elasticity factor. A way to obtain it will be examined in this paper: price and power absorption variations will be considered because it is defined as the ratio of their relative variations before and after DR. This work focuses on the profiles of price variations P with respect to the absorbed power variation Q: users indeed are expected to vary their consumptions according to different values of remunerations. Moreover, different ranges of elasticities have been evaluated in order to study the behavior of P profiles for the more representing users. Finally, effects of a wrong interpolation have been discussed in order to see their consequences on the actual available power.